MORPHOMETRIC ANALYSIS OF PLACENTAL AND M1/M2 MACROPHAGES POLARIZATION IN THE DETECTION OF FETAL GROWTH RESTRICTION - Berezhna, V.A.; Gromova, A.M.; Mamontova, T.V.; Udovytska, N.O.; Starchenko, I.I.; Vesnina, L.E. (World of Medicine and Biology, 2020)
The purpose of the present study was to analyzed the morphometric characteristics and CD68 and CD163 expression of macrophages in the placentas of women, whose pregnancies were complicated by fetal growth restriction. The study revealed low indices of the mass and area of the placentas, but high indices of the fetoplacental weight ratio. The level of CD68+ macrophages in fibrously altered terminal villi of the placenta was significantly higher in both groups women whose pregnancies were complicated by fetal growth restriction. There was significant increased CD163+ macrophages in fibrously altered terminal villi. Thus, in the placentas of women whose pregnancy was complicated by fetal growth restriction and resulted preterm birth, there were disruptions of the vascular and stromal component of the chorionic villus with the changes to macrophage polarization from M1 to M2 types in fibrously altered terminal villi of the placenta.
Keywords: fetal growth restriction; preterm and term birth; placental morphometry; M1 and M2 macrophages